Separation of Y-chromosomal haplotypes from male DNA mixtures via multiplex haplotype-specific extraction. (November 2015) - Rothe, Jessica; Nagy, Marion
Highlights: We designed multiplex HSEs for the separation of male DNA mixtures before Y-STR analysis. We demonstrated the separation of a Y-chromosomal haplotype consisting of six Y-STR markers. We evaluated the maximal distance between extraction site and marker up to 50 kb. We evaluated a minimal DNA input between 50 and 5 ng. Abstract: In forensic analysis, the interpretation of DNA mixtures is the subject of ongoing debate and requires expertise knowledge. Haplotype-specific extraction (HSE) is an alternative method that enables the separation of large chromosome fragments or haplotypes by using magnetic beads in conjunction with allele-specific probes. HSE thus allows physical separation of the components of a DNA mixture. Here, we present the first multiplex HSE separation of a Y-chromosomal haplotype consisting of six Yfiler short tandem repeat markers from a mixture of male DNA.